Dinâmica de valorização do solo urbano próximo de unidades de conservação – estudo de caso do bairro de Campo Grande, município do Rio de Janeiro - Pereira, Eloisa da Silva; Deus, Leandro Andrei Beser de; Ribeiro, Marta Foeppel; Costa, Vivian Castilho da (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2021)
The Campo Grande Urban Structuring Plan (PEU) in the city of Rio de Janeiro establishes guidelines about land use and occupation and defines parameters that help restrain urban expansion towards conservation units - APA Gericinó/Mendanha and Pedra Branca State Park (PEPB). The district is an important economic hub, attracting people, infrastructure and services, and PEPB is attractive to the middle-class real estate market, while the lower income levels move toward the APA. In this way, it can be said that the PEU opened new fronts of urban expansion, accompanying an increase in the intensity of land use and occupation. In this context, it is worthwhile to mention that the opening of spaces to receive projects from the “Minha Casa Minha Vida” Program (PMCMV). This paper aims to analyze the housing growth towards the two conservation units, also seeking to create a future scenario for 2026, through the Land Change Modeler (LCM) tool, from the Idrisi software. It is intended to discuss how such changes have reinforced socio-spatial segregation and impacted the conservation units in the study area. The results indicate there was a greater loss of natural vegetation towards PEPB, with an increase of high standard residences, while towards APA, there was little loss of natural vegetation and increase of popular residences.